Leaving the "peer" out of peer-editing: Online translators as a pedagogical tool in the Spanish as a second language classroom. - Maite Correa (Universidad de La Sabana, 2014)
If you can not beat them, join him [sic] (Google Translation of Si no puedes con tu enemigo, únete a él). Academic dishonesty is widespread in schools and colleges across the world, and with the advent of technology, cheating is easier than ever: While computers and the internet provide students with all the tools they need to plagiarize from the comfort of their own home, instructors find themselves playing "forensic linguist" in order to gather evidence of cheating. Academic dishonesty in the foreign language classroom is not that different from academic dishonesty in other disciplines except for two areas: unauthorized editing by a proficient/native speaker and the use of online translators (OTs). While these two are not usually an issue for assignments in chemistry or psychology, they are two well-known types of academic dishonesty in the foreign languages. In this paper, I examine the use of OTs: how are they different from an online dictionary? How can they be detected? How can their use be prevented? Finally, I propose using them as part of the class in order to discourage/minimize academic dishonesty and raise metalinguistic awareness.